Laser analgesic during orthodontic therapy - Peševska Snežana; Kesić Ljiljana; Ivanovski Kiro; Pandilova Maja; Georgieva Silvana; Mindova Sonja; Ristoska Stevica; Stefanovska Emilija; Curcieva-Cuckova Gabriela; Apostolova Gordana; Maneva Marija; Koneski Filip (Medicinski fakultet i Klinika za stomatologiju, Niš, 2017)
Introduction: Most of the patients feel pain 4 hours after the arch applying, gaining the highest level after 24 hours and its lowering in the next few days. Literature reports show that the fear of pain is a very important reason for discouraging the patient to agree for this kind of orthodontic treatment The aim of this study was to evaluate the effectiveness of the biostimulative laser treatment in pain reduction in patients with fixed orthodontic appliances. Materials and methods. Fifteen patients were treated with low energy level biostimulative diode laser, used 2 minutes per quadrant immediately after placement of fixed orthodontic appliances and in the following four days. The control group of 15 patients received analgesic therapy for period of five days. The pain was assessed subjectively as strong, medium or no pain. The pain disappeared in 20% of the subjects in the examined group after the first day, while in 60% and 26.6% of the subjects medium and isolated pain was still present at day 2 and 3, respectively. Results. The pain disappeared in all the patients treated with laser at day 5. In the control group, strong pain was present in all the subjects the first day, decreasing to 60% of strong pain and 20% medium pain the second day. After day three, the control group demonstrated medium localized pain in 40% of the cases, which dropped to 26.6% after the fourth day, suggesting delayed pain reduction, compared to the laser treated group. Conclusion. Our results suggest that the low energy laser treatment can successfully be used for pain reduction during the initial discomfort period after placing fixed orthodontic appliances.